Предмет: Математика,
автор: Astiushka17
(x^2 +x) ^2 +|x^2 +x|-2=0
Ответы
Автор ответа:
0
Преобразуем уравнение: (x^2-6x)^2+2(x-3)^2=81 --> (x^2-6x)^2+2((x^2-6x)+9)=81 -->
(x^2-6x)^2+2(x^2-6x)^2-63=0
Обозначим Y = (x^2-6x)^2, получим Y^2+2Y-63=0
(x^2-6x)^2+2(x^2-6x)^2-63=0
Обозначим Y = (x^2-6x)^2, получим Y^2+2Y-63=0
Похожие вопросы
Предмет: Математика,
автор: vika8kor129
Предмет: Алгебра,
автор: buranbaevdaniyar
Предмет: Физика,
автор: Аноним
Предмет: Математика,
автор: girdeika
Предмет: История,
автор: katrintug